Genetic and environmental causes of variation in gestation length of Jersey crossbred cattle - Kumar, Anshuman (Vet World, 2016)
AIM: The objective of this study was to investigate the effect of genetic and non-genetic factors and estimate the genetic parameter for gestation length (GL) of Jersey crossbred cattle. MATERIALS AND METHODS: The data included the 986 parturition records on Jersey crossbred cattle maintained at the Eastern Regional Station of ICAR-National Dairy Research Institute, Kalyani, West Bengal, India during 36 years (1978-2013). The data were analyzed applying mixed model least square technique considering the fixed effects of genetic group, season of calving, period of calving, parity of animal, birth weight, and sex of calf born from animal. The effect of sire was included as a random effect in the model. RESULTS: The genetic group of animal, season of calving, parity of animal, and birth weight of calf born were found to be a significant source of variation in the GL, whereas the period of calving and sex of calf did not affect this trait. Cows with <50% and >62.5% Jersey inheritance had the shortest and longest GLs, respectively. Cows calved in summer and rainy season had shorter GL than those calved in the winter season. Older cows in 4(th) parity carried calves for longer days than the cows in 1(st) parity. The increase in calf birth weight significantly (p<0.01) contributed to a linear increase in GL value in this study. The heritability estimate of GL was 0.24±0.08. CONCLUSION: It can be concluded that selection for lower GL without distressing future growth of calf can be used to reduce calving difficulty, but a very small standard deviation of GL limits the benefit. Moreover, more accurate prediction of calving date will help in better management and health care of pregnant animals.